User satisfaction analysis of the final project feature using IPA (importance performance analysis) and EUCS (end user computing satisfaction) case study: academic portal system of Ahmad Dahlan University - Sumagita, Meiliana; Dirgahayu, Raden Teduh (Institute of Computer Science (IOCS), 2024)
This study evaluates the final project feature on the Academic Portal System of Ahmad Dahlan University (UAD) which is divided into 5 sub-features; final project topic registration, final project guidance, logbook, proposal seminar registration, and final project exam registration using Importance-Performance Analysis (IPA) and End-User Computing Satisfaction (EUCS) methods. Data were collected from student users through questionnaires using the IPA method which measures aspects of importance and performance, and the EUCS method which measures user satisfaction with a 1-5 Likert scale. The findings using the IPA method show that although the final project guidance sub-feature has a high level of importance (4.42), its performance is still poor (2.43) and falls into quadrant 1, making it a priority for improvement. In more detail using EUCS method, weaknesses were identified in completeness (2.75) in the Content dimension and accuracy of information (2.69) in the Accuracy dimension, as well as IT service support (2.75) across all dimensions. It is concluded from the results of this study that the IPA and EUCS methods are very relevant and worthy of being used to evaluate the final project features on the UAD Academic Portal System by providing accurate and comprehensive results, so that they can provide a complete picture and technical recommendations on user satisfaction and help identify areas that need to be improved